2022
DOI: 10.1002/cbdv.202100910
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Compositions and Biological Activities of Essential Oils from Four Citrus Species: Citrus limon, Citrus sinensis, Citrus paradisi, and Citrus reticulata

Abstract: Species of the genus Citrus are cultivated in many regions of China and are widely used for medicinal purposes. In the present study, essential oils (EOs) were extracted from four different Citrus species using steam distillation. The chemical components of these four essential oils were separated using gas chromatography‐mass spectrometry, and 52 compounds were confirmed. D‐limonene was found to be the most abundant compound. All four essential oils demonstrated varied but remarkable radical scavenging capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Fingerprint analysis combined with clustering analysis could distinguish QAF from other Rutaceae herbs in a holistic perspective [ 40 ], but the analysis of differential components was missing. Flavonoids and volatile oils could also be used as signature components to distinguish herbs of the Rutaceae family [ 41 , 42 ], which was consistent with our results. In addition, the result of OPLS−DA showed that coumarins and limonoids could also be used as markers to distinguish QAF from AF.…”
Section: Resultssupporting
confidence: 90%
“…Fingerprint analysis combined with clustering analysis could distinguish QAF from other Rutaceae herbs in a holistic perspective [ 40 ], but the analysis of differential components was missing. Flavonoids and volatile oils could also be used as signature components to distinguish herbs of the Rutaceae family [ 41 , 42 ], which was consistent with our results. In addition, the result of OPLS−DA showed that coumarins and limonoids could also be used as markers to distinguish QAF from AF.…”
Section: Resultssupporting
confidence: 90%
“…The tannins, the compounds with more expressive concentration in the C. limon extract, are constituted by complex structure molecules (BULE et al, 2020;SAHAKYAN et al, 2020), which permits the easier interaction with proteins, enzymes and alkaloids (EMAM & IBRAHIM, 2020), so that their different forms can have different biochemical effects in herbivore arthropods, causing mortality and deterrence (CHEN et al, 2022). Therefore, tannins can act as endogenous growth inhibitors (EL-ASWAD et al, 2023), anti-nutritional substances and can also act in the defense against biotic and abiotic stresses (PRATYUSHA, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The primary constituents identi ed were limonene (88.25%), terpinen-4-ol (1.98%), β-myrcene (1.90%), and linalool (1.50%). Similarly, in Guangdong, China, Li and colleagues [40] conducted a characterization of the Citrus sinensis peel oil, revealing the presence of 28 components accounting for 85% of the total essential oil. Notably, the key components in this case were d-limonene (49.14%), neral (9.54%), and eucalyptol (3.55%).…”
Section: Chemical Compositionmentioning
confidence: 99%